Dual Role of Indoles Derived From Intestinal Microbiota on Human Health - Ye, Xuewei; Li, Haiyi; Anjum, Komal; Zhong, Xinye; Miao, Shuping; Zheng, Guowan; Liu, Wei; Li, Lanjuan (Frontiers in Immunology, 2022)
Endogenous indole and its derivatives (indoles), considered as promising N-substituted heterocyclic compounds, are tryptophan metabolites derived from intestinal microbiota and exhibit a range of biological activities. Recent studies indicate that indoles contribute to maintaining the biological barrier of the human intestine, which exert the anti-inflammatory activities mainly through activating AhR and PXR receptors to affect the immune system’s function, significantly improving intestinal health (inflammatory bowel disease, hemorrhagic colitis, colorectal cancer) and further promote human health (diabetes mellitus, central system inflammation, and vascular regulation). However, the revealed toxic influences cannot be ignored. Indoxyl sulfate, an indole derivative, performs nephrotoxicity and cardiovascular toxicity. We addressed the interaction between indoles and intestinal microbiota and the indoles’ effects on human health as double-edged swords. This review provides scientific bases for the correlation of indoles with diseases moreover highlights several directions for subsequent indoles-related studies.